The Effects of Making Public Service Employees Aware of Their Prosocial and Societal Impact: A Microintervention. (18th January 2020) - Vogel, Dominik; Willems, Jurgen
Abstract: Over the past decade, practitioners and scholars have intensified the discussions around people's expectations from their jobs and how public and private organizations can succeed in the war for talent. In this context, it has become obvious that people not only seek high salaries and career opportunities but also meaningfulness in their daily tasks. Although many public service jobs offer opportunities to help others (prosocial impact) or contribute to society (societal impact), employees tend to become accustomed to these positive aspects or forget about them. This article tests whether a microintervention that emphasizes employees' prosocial or societal impact can positively affect their well-being, intention to stay in the job, and willingness to recommend their respective jobs to others. The combined results of three preregistered experiments reveal that microinterventions can indeed have these effects, particularly if they focus on creating awareness about the jobs' societal impact.